Pengarsipan digital produk informasi - Siti Fatimah Sembiring (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2016)
This article discusses developing a framework that considers digital archiving as a form of information production network, where various stages generate modulated digital archives and distributed in a variety of actors.